Face recognition by neural network using bit-planes extracted from an image - Ting, K.C; Tan, J.Y.B.; Lee, T.Z; Bong, David B L (Binary Information Press, 2013)
An 8-bit digital image consists of 256 levels of gray-value and 8 layers of multilevel information of bits known as bit-plane information. A novel method utilizing higher order bit-plane information that contains majority of visually signi_cant data and dummy blank images as inputs to a multilayer feedforward Neural Network (NN) is proposed in this paper to perform face recognition. Experiments performed on the proposed face recognition model using two face databases, namely CMU AMP face expression database and Yale face database, show improvement in recognition rate compared to using only gray-level images as inputs to the NN.